(untitled) (Jurnal Pembangunan Sosial, 2010)
Theory is important to help counselor building rapport with client, helping client to identify and solve problem, as well as helping client to conceptualize and to synthesize their problem. The aim of this study is to identify the factors of choosing counseling theory and the role of counseling theory among counselors in Kuala Lumpur. The design of this research is a case study. A total of six counselors who have private practice were chosen as research’s participants. The data were collected by using interview protocol, and being analysed through the thematic approach. The findings of this study show that the factors which influence them to choose counseling theory are the influence of their personality, the influence of their lecturer or supervisor, the influence of their upbringing, the influence of principles of life, and the influence of theory proponents. This study also points out that counseling theory can help them building rapport with client, helping them to solve problem, helping their client to identify their problems, and helping their client to conceptualize and to synthesize problem. As a whole, counseling theory is considered important to every counsellor in this study.